2013
DOI: 10.1089/dna.2013.1997
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin 18, Interleukin 2, and Tumor Necrosis Factor Polymorphisms with Subacute Sclerosing Panencephalitis

Abstract: Subacute sclerosing panencephalitis (SSPE) is a progressive inflammatory and degenerative disorder of the central nervous system. The measles virus (MV) and host and environmental factors are involved in the development of SSPE, but the precise mechanism by which the MV causes SSPE is still unknown. Studies have indicated that in SSPE patients, specific polymorphisms of certain genes are most likely involved in impairing the host's ability to eradicate the MV. The purpose of our study was to elucidate the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Variability in the global incidence of SSPE also indicates that genetic factors are involved. Many case‐control studies (mostly done in Turkey and Japan) observed genetic defects in components of innate immunity, including Toll‐like receptors and cytokines …”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…Variability in the global incidence of SSPE also indicates that genetic factors are involved. Many case‐control studies (mostly done in Turkey and Japan) observed genetic defects in components of innate immunity, including Toll‐like receptors and cytokines …”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…Five SNPs in the promoter region of IL18 gene (11q22.2-q22.3) have been described: -656 G/T, -607 C/A, -137 G/C, 113 G/T and 127 C/T (Giedraitis et al, 2001). However, only the SNPs at positions -137 G/C and -607 C/A were confirmed as having an impact on the activity of IL18 gene in previous studies (Piskin et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, some studies have reported associations between SSPE and single nucleotide polymorphisms (SNPs) of genes in the host immune system. These include SNPs in genes related to innate immunity such as MxA [41], tolllike receptor 3 (TLR3) [42], and TLR4 [43], and in those related to acquired immunity such as interleukin-2 (IL2) [44], IL4 [45], IL17 [43], IL18 [46], granzyme B (GZMB) [47], and programmed cell death 1 (PDCD1) [48]. Quantitative or qualitative differences in immune response to the measles virus caused by these SNPs may be related to disease susceptibility to SSPE.…”
Section: Inosine Pranobexmentioning
confidence: 99%